Enhancement of cisplatin-based TACE by a hemoglobin-based oxygen carrier in an orthotopic rat HCC model. (August 2014) - Liu, Xiao-Bing; Cheng, Qiao; Geng, Wei; Ling, Chang-Chun; Liu, Yan; Ng, Kevin Tak-Pan; Yam, Judy Wai-Ping; Guan, Xin-Yuan; Lo, Chung-Mau; Man, Kwan
Abstract Objective: Hypoxic tumor cells are more resistant to standard chemotherapies. A number of studies indicated that improving oxygenation inside the tumor could serve as a potential strategy to target hypoxia-induced chemoresistance. In this study, we examined whether a hemoglobin-based oxygen carrier (OC89) could increase tumor oxygenation and thus enhance the efficiency of transarterial chemoembolization (TACE) in an orthotopic rat HCC model. Methods: Efficiency of the hemoglobin-based oxygen carrier (OC89) in improving tumor oxygenation was examined by OxyLab pO2. Sensitization of chemotherapy (cisplatin) in TACE by OC89 was evaluated in four different therapeutic regimens including cisplatin (1 mg/kg) + OC89 (0.2 g/kg), cisplatin (1 mg/kg) + OC89 (0.4 g/kg), cisplatin (3 mg/kg) + OC89 (0.2 g/kg), cisplatin (3 mg/kg) + OC89 (0.4 g/kg). For all the therapeutic regimens, a single delivery of OC89 via the tail vein was performed 1 h before TACE. Results: Compared with Ringer's buffer, systemic delivery of OC89 (0.4 g/kg) attenuated tumor hypoxia (p < 0.05). Additionally, partial pressure of oxygen (pO2) fraction of low readings (0–10 mmHg) inside the tumor decreased from 74.1% to 24.6% after OC89 delivery, while pO2 fraction of high readings (15–25 mmHg) increased from 22.2% to 41.5%. When cisplatin was combined with OC89, regimen cisplatin (3 mg/kg) + OC89 (0.4 g/kg) resulted in a significant inhibition of tumor growth at Day 21 after therapy (p < 0.05). Further investigation indicated that OC89 delivery influenced anti-apoptotic and pro-apoptotic balance of the UPR pathway in the tumor. Conclusions: Our data suggest that targeting tumor hypoxia with the hemoglobin-based O2 carrier serves as a promising approach to enhance the efficacy of cisplatin-based chemotherapy in HCC.